The interactive impact of Arrogant Leadership in Organizational Cynicism An exploratory Study in a sample of populace institutions -Zakho independent administration - Jameel, Farhad; Ahmed, Hashem; Rashid, Rewar (Humanities Journal of University of Zakho, 2022)
The current research aims to Recognition on The interactive impact of Arrogant Leadership in Organizational Cynicism in populace institutions -Zakho independent administration. The research depends on a set of main and sub hypothetical which practically tested in a random sample of institutions under research, The questionnaire was used as a basic tool to collect the data required to complete the field side of the research, the questionnaire consisted of (27) items, and (130) questionnaires were distributed to the administrative personnel at populace institutions -Zakho independent administration, the number of valid questionnaires for analysis purposes was (120) questionnaire. A set of statistical methods were used to analyze the data and arrive at the required results, such as: frequencies, percentages, mean, standard deviation, (T) & (F) test in (SPSS V. 21). The research came to a number of conclusions; the most important one is the existence of a positive significant correlation and effect between Arrogant Leadership in and Organizational Cynicism of institutions under research. Finally, this research has Its informal expression, some points were suggested for the institutions under research which are The need for the Zakho independent administration team Follow up managers dealing with employees through supervisory committees and field visits and develop them through preparing administrative and leadership courses or workshops to enhance their skills and direct employees in a positive direction that will develop the spirit of loyalty and commitment in those institutions.